(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
The up to 1200 m thick Norian succession of the Quattervals Nappe (Central Austroalpine, Italy) documents a tectonically-driven passage from intertidal facies (Dolomia Principale-Hauptdolomit), represented by early-dolomitized bedded to massive gray dolostones, to intraplatform basin sediments (Pra Grata Formation and Quattervals Limestone), consisting of resedimented dark limestones and thin bedded laminated limestones, alternating (mainly in the Pra Grata Formation) with intraformational breccias containing abundant shallow-water facies. The transitional and basinal facies contain an interesting ostracod assemblage, beside bioclastic layers containing shallow-water and upper slope skeletal grains.The ostracod fauna is rich in specimens belonging to few genera, denoting restricted environmental conditions characterized by variations of salinity and low oxygenation. Despite the intense deformation and recrystallization related to the Alpine tectonics, the paleontological analysis of the ostracod assemblage from the base of the Quattervals Limestone, allowed the identification of the two new species of ostracods Rhombocythere dimorphica and Kerocythere quattervalsi in association with other already known forms.